When Death Was Postponed: The Effect of HIV Medication on Work, Savings, and Marriage - Mette Ejrnæs; Esteban García-Miralles; Mette Gørtz; Petter Lundborg (Institute of Labor Economics (IZA), 2023)
Longer life expectancy can affect individuals' incentives to work, save, and marry, net of any changes in their underlying health. We test this hypothesis by using the sudden arrival of a new treatment in 1995 that dramatically increased life expectancy for HIV-infected individuals. We compare the behavioral responses of HIV-infected individuals who were still in good health but who differed in their access to the new treatment. Those with access to treatment work substantially more, marry later, but do not save more. Our results highlight the importance of accounting for such incentive effects when valuing increases in life expectancy.
Keywords: D84; I12; J12; J21; 330; life expectancy; labor supply; marriage; HIV